Analysis of the Influence of Environmental Factors on Communication Development and Self-Confidence in 2 Years Old Children - Maulana, Aditia Hendri; Aini, Alvita Farha; Kurniawati, Sita Ardelia; Nargis, Nargis (Indonesian Journal Publisher, 2024)
The purpose of this study was to track and assess the development of communication, self-confidence, and the influence of environmental factors in a two-year-old child. This case study investigated a child named Bara through direct observation for two hours in the playground and home environment on June 15–16, 2024. Direct interaction with the subject and observation were part of the data collection process. The results showed that Bara had age-appropriate communication skills, including understanding basic instructions and using simple words and sentences. Bara showed confidence in various activities and interactions with adults. Bara found that his home and social environment, with adequate stimulation and positive interactions, were very supportive of his growth. The study found that Bara has developed in communication and self-confidence at a good level, with significant support from environmental factors. Suggestions for further development include enriching language, increasing self-confidence, and making the supportive environment more optimal.